Enhancing Descriptive Statistics Learning through Project-Based Learning (PjBL) for Islamic Education Management Students - Ali Umar; Nurul Qomariyah Ahmad; Firmansyah B; Nur Ainun Lubis (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
Educational statistics is a crucial course that students of Islamic Education Management must master. However, students whose majors are not directly related to mathematics often face difficulties in learning educational statistics. Therefore, it is necessary to develop a learning model that can improve students' understanding and is applicable to practical courses such as educational statistics. One promising alternative is the Project-Based Learning (PjBL) model. This study was conducted at IAIN Takengon Aceh and involved 23 fourth-semester Islamic Education Management students in the 2023/2024 academic year. The research data were collected in the form of video recordings, photos, and final project reports. The data were analyzed using qualitative techniques and presented through narrative description. The results showed that the PjBL model is effective in promoting an understanding of descriptive statistics, fostering collaboration, and providing opportunities for students to develop problem-solving skills